Taxing the Digital Economy: Bridging the Impact of E-Commerce Tax Regulations on Taxpayer Compliance - Ramadanty, Jesica; Fuadah, Luk Luk (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study investigates the effectiveness of e-commerce tax regulations in enhancing taxpayer compliance by conducting a systematic literature review of 20 academic articles published between 2019 and 2025. With the rapid growth of the digital economy, governments across developed and developing countries have introduced new legal frameworks to address the taxation challenges associated with online transactions. This study identifies key regulatory, institutional, and behavioral factors that influence taxpayer compliance in e-commerce contexts. The findings reveal that tax knowledge, regulatory clarity, service quality, and enforcement mechanisms such as audits and penalties positively influence compliance. However, challenges such as regulatory complexity, low tax literacy, limited digital infrastructure, and cross-border enforcement remain persistent barriers, especially in emerging economies. This study also highlights significant differences in regulatory approaches across regions, with Southeast Asian countries such as Indonesia and Malaysia taking proactive steps to bridge tax policy and digital trade. The study concludes that successful implementation of e-commerce tax regulation depends not only on legal mandates but also on the perceived fairness, efficiency, and accessibility of tax systems. The findings provide practical insights for policymakers to enhance tax compliance by focusing on simplification, education, and trust-building strategies in the digital economy.